Internalization of The Character of Love for The Motherland in Prospective Health Workers through PAI Courses in College (Analytical Descriptive Study at Stikes Karsa Husada Garut) - Supriyanto, Irwan; Suresman, Edi; Ganeswara, Ganjar Muhammad (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
Nurturing the value of love for the motherland is mandatory in higher education, including STIKes students. This study aims to analyze the planning, process, and results of internalizing the character of love for the motherland in prospective health workers through PAI courses at STIKes Karsa Husada Garut College. The research employed a qualitative approach and descriptive method. The study showed that: 1) the planning carried out by PAI lecturers in internalizing the character of patriotism was still in the form of a hidden curriculum, not specifically written in the RPS, 2) the implementation was good enough based on the indicators of the character of patriotism, 3) the results of the internalization of the character of patriotism based on the indicators had been internalized. However, STIKes Karsa Husada needed to make a detailed curriculum regarding the internalization of the character of love for the motherland through PAI courses. Thus, it can be a reference for lecturers in making plans so that implementation and evaluation can be maximized.